2017
DOI: 10.1136/bmjopen-2016-013113
|View full text |Cite
|
Sign up to set email alerts
|

What proportion of patients with psychosis is willing to take part in research? A mental health electronic case register analysis

Abstract: ObjectiveThe proportion of people with mental health disorders who participate in clinical research studies is much smaller than for those with physical health disorders. It is sometimes assumed that this reflects an unwillingness to volunteer for mental health research studies. We examined this issue in a large sample of patients with psychosis.DesignCross-sectional study.SettingAnonymised electronic mental health record data from the South London and Maudsley NHS Foundation Trust (SLaM).Participants5787 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
0
24
1
Order By: Relevance
“…(15) In studies of other psychiatric illnesses, recruitment rates vary widely between 35% and 68%. (10,13,16) In terms of retention, 70% of the recruited participated remained in the TOB study. This is similar to ndings from a meta-analysis of psychotherapy trials for BPD, which reported an overall retention rate of 71-75%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(15) In studies of other psychiatric illnesses, recruitment rates vary widely between 35% and 68%. (10,13,16) In terms of retention, 70% of the recruited participated remained in the TOB study. This is similar to ndings from a meta-analysis of psychotherapy trials for BPD, which reported an overall retention rate of 71-75%.…”
Section: Discussionmentioning
confidence: 99%
“…17However, studies on psychotic disorders had found that younger patients are more likely to participate in research studies compared to older patients. (12,13) In terms of clinical variables, a meta-analysis found that commitment to change, low impulsivity, and strong therapeutic relationship were predictive of retention among patients with BPD. (17) In studies of psychotic disorders, patients with higher illness severity, suicidality, longer length of hospitalization, and medical comorbidities were less likely to be approached about study participation (13) and more likely to decline participation when approached.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, only few persons are approached for consent to participate, tending researchers to involve less severely ill and with better outcomes patients with possible recruitment bias (Patel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%